Влияние вторичных дефектов на надежность динамичных информационных систем - Маевский, Д. А. (НТУ "ХПИ", 2012)
Проведены исследования влияния вторичных дефектов в программном обеспечении динамичных информационных систем на их надежность. Выявлена и исследована тенденция увеличения количества вторичных дефектов на начальной стадии процесса тестирования, что негативно влияет на надежность

Studies of influence of secondary defects are undertaken in software of the dynamic information systems on their reliability. The tendency of increase of amount of secondary defects is educed and investigational on the initial stage of testing process, that negatively influences on reliability
Influence of secondary defects on reliability of dynamic information systems
Keywords: программное обеспечение; теория динамики; математическое моделирование; неравновесные системы; reliability of software; secondary defects; theory of dynamics of the programming systems; dynamic information systems